Oral Health Knowledge, Attitudes, and Practices among Pregnant Women in Routine Prenatal Care in South China: A Cross‐Sectional Survey - Xiaojie Lin; Lanlan Jiang; Zhenhua Pang; Sumei Wang; Qixin Zeng; Zuke Ya; Yuanyuan Peng; Yuxiao Huang; Qiaozhi Jiang; Renchuan Tao (Special Care in Dentistry, 2026)
ABSTRACT Background Physiological changes during pregnancy can increase the risk of oral diseases in women, which may directly affect the health status of their newborns. This cross‐sectional study aims to assess the oral health knowledge, attitudes, and practices of pregnant women in South China, as well as their associated factors. Methods A cross‐sectional survey on oral health was carried out between June 2016 and June 2017. The study involved 517 pregnant women recruited from the First Affiliated Hospital of Guangxi Medical University and Hospital of Stomatology, Guangxi Medical University during their visits for either routine prenatal care or dental services. Results According to the survey, while over 90% of pregnant women recognized the importance of regular brushing and gargling, only approximately half were aware of the benefits of pit and fissure sealants (50.3%) and fluoride treatments (48.4%). Moreover, merely 9.3% had undergone routine dental check‐ups before pregnancy. In terms of daily oral hygiene, 87.2% reported brushing at least twice daily, yet the proportions incorporating flossing (17.8%) and gargling (43.7%) were considerably lower. Multivariate analysis showed that older age, urban residency, nulliparity, higher education and dental insurance were factors potentially associated with better oral health knowledge, attitudes, and practices (all p < 0.05). Of note, education and method of dental payment consistently exhibited positive effects across multiple models. Conclusions In conclusion, while the majority of pregnant women possessed satisfactory oral health knowledge, their practical implementation of specific oral hygiene measures and routine dental attendance were insufficient. Education and dental payment method may play a pivotal role in shaping oral health knowledge, attitudes and practices.